The injury characteristics of open pilon fractures predictive of complications. Issue 4 (April 2022) - Heiner, Jacob A.; Banner, Katherine A.; Wu, Victor J.; Achor, Timothy S.; Gary, Joshua L.; Munz, John W.; Choo, Andrew M.; Kellam, James F.; Warner, Stephen J.
Highlights: Open pilon fractures are severe, limb-threatening injuries and are at risk for wound complications requiring return trips to the operating room. The OTA open fracture classification is an additional tool to assist in stratifying and assessing the severity of an open pilon injury. In our cohort, a patient was at risk for an early amputation if they presented with segmental bone loss (OTA-OFC bone loss grade 3). Major wound complications occurred with: fall > 3 m, multifragmentary articular surface, segmental fibula fracture, or OTA-OFC contamination grade 3. Abstract: Objective: Determine predictive injury factors for wound complications in open pilon fractures (OTA/AO 43B and 43C). Design: Retrospective Case Series. Setting: Level I Trauma Center. Patients/participants: A total of 61 open pilon fractures in 60 patients were evaluated after meeting inclusion and exclusion criteria. Intervention: The majority of injuries underwent a staged protocol with immediate antibiotics, debridement, irrigation and external fixation. Following soft tissue stabilization, internal fixation was performed and wound closure achieved in a coordinated fashion depending on the type of closure required. Main outcome measurements: Early amputation rate, 90-day major (wound dehiscence or deep infection requiring operative intervention) and minor (superficial infection) wound complications. Results: Four patients incurred early amputations, 11 had major wound complications and 5 had minor wound complications. An early amputation was more likely if they presented with an OTA Open Fracture Classification (OTA-OFC) Bone Loss Grade 3. A major wound complication was more likely if they presented with a fall from > 3 m, a multifragmentary articular surface, a segmental fibula fracture, or an OTA-OFC Contamination Grade 3. A multifragmentary articular surface was also predictive of developing any wound complication. Conclusions: Open pilon fractures are severe, limb-threatening injuries and are at risk for wound complications. Patients presenting with these injuries and a predictive factor should be counseled regarding the possibility of early limb loss or experiencing a wound complication that will require additional treatment. Level of evidence: Level III